The ten-thousand year fever : rethinking human and wild primate malarias - Cormier, Loretta A. (Walnut Creek, CA : Left Coast Press, 2011)
"Malaria is one of the oldest recorded diseases in human history, and its 10,000-year relationship to primates can teach us why it will be one of the most serious threats to humanity in the 21st century. In this pathbreaking book Loretta Cormier integrates a wide range of data from molecular biology, ethnoprimatology, epidemiology, ecology, anthropology, and other fields to reveal the intimate relationships between culture and environment that shape the trajectory of a parasite. She argues against the entrenched distinction between human and non-human malarias, using ethnoprimatology to develop a new understanding of cross-species exchange. She also shows how current human-environment interactions, including deforestation and development, create the potential for new forms of malaria to threaten human populations. This book is a model of interdisciplinary integration that will be essential reading in fields from anthropology and biology to public health"--
Introduction: malaria as a primate disorder -- Co-evolution: parasites, vectors, and hosts -- Falciparum type: the great ape malaria -- Vivax type: the macaque malaria -- Migration: malaria in the New World -- Rhesus factor: experimental studies in wild primates -- Ethics: human experimentation -- Future: the primate malaria landscape -- Appendix 1. Plasmodia parasites and their natural primate hosts -- Appendix 2. Experimentally induced plasmodium cross-infections into novel hosts -- Appendix 3. Naturally acquired cross-infections with novel malaria parasites -- Appendix 4. Primate species and all infections with plasmodium parasites.
Includes bibliographical references (p. 183-226) and index.
Machine generated contents note: Preface 1. Malaria as a Primate Disorder 2. Co-Evolution: Parasites, Vectors, and Hosts 3. Falciparum-Type: The Chimpanzee Malaria 4. Vivax-Type: The Macaque Malaria 5. Migration: Malaria in the New World 6. Rhesus Factor: Experimental Studies in Wild Primates 7. Ethics: Human Experimentation 8. Future: The Primate Malaria Landscape Appendix I. Plasmodia Parasites and their Natural Primate Hosts Appendix II. Experimentally-Induced Plasmodium Cross-Infections into Novel Hosts Appendix III. Naturally-Acquired Cross-Infections with Novel Malaria Parasites Appendix IV. Primate Species and All Infections with Plasmodium Parasites References Index.
Machine generated contents note: Preface 1. Malaria as a Primate Disorder 2. Co-Evolution: Parasites, Vectors, and Hosts 3. Falciparum-Type: The Chimpanzee Malaria 4. Vivax-Type: The Macaque Malaria 5. Migration: Malaria in the New World 6. Rhesus Factor: Experimental Studies in Wild Primates 7. Ethics: Human Experimentation 8. Future: The Primate Malaria Landscape Appendix I. Plasmodia Parasites and their Natural Primate Hosts Appendix II. Experimentally-Induced Plasmodium Cross-Infections into Novel Hosts Appendix III. Naturally-Acquired Cross-Infections with Novel Malaria Parasites Appendix IV. Primate Species and All Infections with Plasmodium Parasites References Index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Malaria; Medical parasitology; Primates -- Diseases; Malaria; Primate Diseases; Electronic books